Changing Industrial Relations in Europe - Beaumont, P. B. (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "Changing Industrial Relations in Europe," edited by A. Ferner and R. Hyman.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Changes; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z